PENGARUH IKLAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA MOBIL ALMAZ PT. WULING MOTOR ARISTA DI KOTA BENGKULU - Putra P, Roynaldi; Herfianti, Meiffa (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
The aim of this research is to find out how the influence of Advertising and Brand Image on the decision to buy a car Almaz PT. Wuling Motor Arista in Bengkulu City. The population used in this study were consumers at Almaz PT. Wuling Motor Arista in Bengkulu City totaled 85 respondents. The sampling technique used total sampling based on predetermined criteria totaling 85 respondents. Observation data collection techniques, documentation and questionnaires. The data that has been processed was analyzed using the SPSS 24 formula. The research that has been conducted on the effect of Advertising and Brand Image on Purchasing Decisions on Almaz Cars PT. Wuling Motor Arista in Bengkulu City, it can be concluded as follows: Advertising has a significant effect on Purchasing Decisions on Almaz Cars PT. Wuling Motor Arista in Bengkulu City. Brand Image has a significant effect on Purchasing Decisions on Almaz Cars PT. Wuling Motor Arista in Bengkulu City. Keywords : Advertising, Brand Image, Purchase Decision.